Development of a post-harvest handling and storage procedure for tomatoes (Lycopersicon Esculentum) - Blancaflor, Jennifer Benitez; Dumelod, Benelyn Domingo (1995)
The development of a post-harvest handling and storage procedure for fresh tomatoes was undertaken. The variables studied were packing material and storage treatment. The effects of these on the shelf-life of the fresh tomato were determined through objective and subjective evaluations. Statistical tools such as measures of central tendency, evaluation of reliability, test for precision, and criteria for rejection of suspect values were used to evaluate the data gathered. Two-way ANOVA was also employed to determine the difference among observations due to the variables. In Phase I, a community surveillance was conducted in the area of study--San Miguel, Bulacan. Statistical data and information were obtained and studied. The surveillance results emphasized the clear need for a post-harvest storage facility, and revision of the farmers' harvest and post-harvest handling practices. Data on pH, titrable acidity, and total soluble solids, and subjective evaluations in Phase II showed that polyethylene was the best packing material in extending the shelf-life of tomato. In Phase III, subjective evaluations showed that the use of charcoal as the embedding material for KMnO4 prolonged the shelf-life of tomato even further, for at least one month. Based on the results of Phase II and III, the storage set-up which can maximize the shelf-life of tomato was determined. Results showed that the treatment with two charcoal-clay balls or two KMnO4-dipped charcoal sachets prolonged the shelf-life of tomatoes at light red stage the longest (twenty-one days or three weeks). It is expected that the tomatoes at green/breaker stages of maturity, if subjected to similar storage conditions, will keep longer than three weeks. It is recommended that the two treatments be considered according to their feasibility in the area where they will be applied.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Tomatoes -- Storage